Core binding factor subunit β plays diverse and essential roles in the male germline - Rahmawati, Mustika; Stadler, Kassie M.; Lopez-Biladeau, Blanca; Hoisington, Tia M.; Law, Nathan C. (Frontiers in Cell and Developmental Biology, 2023)
Much of the foundation for lifelong spermatogenesis is established prior to puberty, and disruptions during this developmental window negatively impact fertility long into adulthood.However, the factors that coordinate prepubertal germline development are incompletely understood. Here, we report that core-binding factor subunit-β (CBFβ) plays critical roles in prepubertal development and the onset of spermatogenesis. Using a mouse conditional knockout (cKO) approach, inactivation of Cbfb in the male germline resulted in rapid degeneration of the germline during the onset of spermatogenesis, impaired overall sperm production, and adult infertility. Utilizing a different Cre driver to generate another Cbfb cKO model, we determined that the function of CBFβ in the male germline is likely limited to undifferentiated spermatogonia despite expression in other germ cell types. Within undifferentiated spermatogonia, CBFβ regulates proliferation, survival, and overall maintenance of the undifferentiated spermatogonia population. Paradoxically, we discovered that CBFβ also distally regulates meiotic progression and spermatid formation but only with Cbfb cKO within undifferentiated spermatogonia. Spatial transcriptomics revealed that CBFβ modulates cell cycle checkpoint control genes associated with both proliferation and meiosis. Taken together, our findings demonstrate that core programs established within the prepubertal undifferentiated spermatogonia population are necessary for both germline maintenance and sperm production.